The Social Contract in Miniature: How Virtual Bargaining Supports Team Production - Zeitoun, Hossam; Melkonyan, Tigran; Chater, Nick (Academy of Management Review, 2023)
The ability of teams to self-organize and engage in spontaneous collaboration is crucial to 21st-century organizations. The large extent of nonroutine activities in such organizations hampers the effectiveness of traditional management instruments, such as monitoring effort and performance levels and exercising fiat — resulting in increasingly important self-organized collaboration. To explain how such collaboration is possible, we suggest a refinement of the psychological assumptions underpinning influential theories of the firm — specifically, concerning how people reason. We juxtapose Nash reasoning (the mode of reasoning underpinning organizational economic theories of the firm) with virtual bargaining (a more collaborative mode of reasoning drawing on recent research in cognitive science). Virtual bargaining enables individuals to establish, maintain, and abide by tacit “social contracts” of their team and organization — the (often tacit) norms, rules, roles, and responsibilities governing how employees should behave (irrespective of their personal objectives). Thus, virtual bargaining helps individuals mitigate challenges of team production, such as shirking and hold-up, in a self-organizing and self-enforcing way. We analyze the conditions under which virtual bargaining leads individuals to coordinate on enhanced effort levels in organizationally relevant settings. We outline avenues for empirically testing virtual bargaining in organizations and discuss conceptual implications.